WiFi visualiser : viewing WiFi signal in a pictorial view II - Tan, Heng Yee (2015)
Electromagnetic radiation spread across a wide range in the electromagnetic spectrum and only small portion know as the visible spectrum are naturally visible to the human eye. This project presents a possible solution to view invisible radiation created by WiFi signal of 2.4GHz band. Drawing upon the concept such as thermal imaging which makes it possible to see one’s environment with or without visible illumination by using different colour representation for different temperature range. With that in mind, the visualisation of WiFi signal makes it possible to see its fluctuation in space, strength in particular area, and possible source location. All of these aims to allow reader to better understand the presented information. Furthermore, this project also applies a similar concept of how digital camera image processor works, as well as how image pixel represent the original image. Arduino controller is programmed to control the hardware switching of multiplexer while filtering only the required information. The MATLAB program does the algorithm and assignation of specific colour to the signal strength information it received. The result was output to the monitor screen. The prototype was named WiFi Visualiser. It is an assembly of manufactured parts, recycled materials, off the shelf components for the structural as well as electronic components that were used for the WiFi data acquisition and transmission as well as analysis. The Cantenna is a component of the prototype, made from recycled metallic food can and then modified to the correct size. The can is slitted underneath to allow for the wiring of the antenna to pass through. The antenna would then be precisely positioned inside the can to capture the WiFi signal. Cantenna (a type circular waveguide) which functioned like directional antenna is able to retrieve WiFi signal information in the direction it points to. They were arranged in an array of 4 row x 6 columns on the prototype. The testing was conducted in a large room but confined within a 25m x 20m x 2.5m space with an omnidirectional router placed at a distance (d) away from the WiFi Visualiser. The test collected a total of 5 readings with four readings being taken at a fixed distance but with different orientation angles, and one reading with shortened distance but with a fixed orientation angle. The results show significant consistency and expectation of a directional waveguide function; which is to direct the signal in its pointed direction to the antenna that is inside. The WiFi Visualiser successfully pictorised a 2.4GHz band WiFi signal and the suggested future improvement that includes increasing the speed of output display. This report shall focus on the mechanical construction of the prototype, construction of the Cantenna, and electrical wiring.